Pembuatan biskuit bergizi untuk pemenuhan kebutuhan nutrisi anak balita penderita gizi kurang di Kecamatan Syiah Kuala (Processing nutritious biscuit product as supplementary nutrition for malnourished toddler in Syiah Kuala Sub-District) - Sufiat, Suryati; Lubis, Yanti Meldasari (Universitas Syiah Kuala, 2021)
The aim of this community service activity was to increase the knowledge of health workers and mothers at the integrated healthcare centers (Posyandu) how to make biscuits from banana flour, red bean flour, and green bean flour as a supplementary nutritional product of malnourished toddlers in Syiah Kuala Sub-district. The methods were survey, socialization, and practicing of making biscuits from Awak banana flour, red bean flour, and mung bean flour involving mothers of the toddlers, heads of health centers, and Posyandu cadres. Based on the observation during the programs, the participants were very disciplined and enthusiastic in participating in all activities. Also, the participants were capable of making the biscuits product. Based on the proximate analysis conducted at the Laboratory of Baristand (Research and Standardization Center) in Banda Aceh, every 100 grams of the biscuit contains the nutritional content of carbohydrates 29.98%, protein 6.57%, fat 37.28%, water content 0.58%, ash content 1.72%, and calories 328.17 kcal. It can be concluded that 100 grams of biscuitcan supply the nutritional needs of malnourished toddlers as much as 328.17 kcal from the dietary needs of 1.620 kcal per day.